2016
DOI: 10.1089/acm.2015.0200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of Adipose Tissue in Obese Women in Response to Acupuncture Catgut Embedding Therapy with Moxibustion

Abstract: The effects of ACET with moxibustion on body weight and insulin resistance were associated with the regulation of biochemical events that are altered in obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In addition, it is not associated with apparent radiculopathies or myelopathies. 6,7 Thread-embedded acupuncture (TEA) has been used for the treatment of musculoskeletal pain, 8 obesity, 9 and sequelae of facial palsy 10 in East Asian countries. It is a special method of treatment involving acupuncture, in which polydioxanone is injected into the subcutaneous or muscle layer at specific acupoints, which provides longlasting pain control effect compared to dry needling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is not associated with apparent radiculopathies or myelopathies. 6,7 Thread-embedded acupuncture (TEA) has been used for the treatment of musculoskeletal pain, 8 obesity, 9 and sequelae of facial palsy 10 in East Asian countries. It is a special method of treatment involving acupuncture, in which polydioxanone is injected into the subcutaneous or muscle layer at specific acupoints, which provides longlasting pain control effect compared to dry needling.…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing is a new technical method that locates and quanti es the transcriptome through microarrays, which can digitally measure the existence and prevalence of transcripts 13,14 . Recent transcriptomic studies have found that acupuncture affects the mRNA levels of multiple differentially expressed genes (DEG) in the brain of the rat and regulates multiple biological processes, including in ammation, oxidative stress, and vascular endothelial function 15,16 . However, it has not been reported which signaling pathways and genes in speci c brain regions are affected by MA at KI3.…”
Section: Introductionmentioning
confidence: 99%
“…9 TEA has been widely used in recent years, and its continuous stimulating effect is considered to allow long-term effects to be maintained with relatively few treatments. 10 Recently, many studies investigated TEA using catgut in other countries, [11][12][13] while, in the Republic of Korea, polydioxanone (PDO) TEA is mainly used. PDO is a synthetic absorbable suture, which is absorbed completely within 180 days via hydrolytic degradation, whereas catgut is digested by proteolytic enzymes in the body.…”
mentioning
confidence: 99%